Cyberspace as apparatus an exploration of film apparatus theory in a massively multiplayer online role-playing game - Ham, Jongsuk 1981-
"The same apparatus principle that once created the theoretical simulacrum in Plato's Cave is manifested in the whole new virtual world of online cyberspace in the late 20th century. the impression of reality on the wall of Plato's Cave that dazzled the prisoners has become more than a fleeting impression in cyberspace. Now the viewers' perception and actually dwell within its impression of reality and it makes them turn into players with the capability of intervention in the reality. However, existing studies on online visual cyberspace have focused mainly on the bahvior of players, ignoring the potential effect of visual images. Cyberspace can basically be understood as virtual space comes from the visual images that the apparatus creates, the behavior of players would certainly be affected by it. Thus, this study aims to examine the possible effects of visual images in cyberspace through apparatus theory in film. The specific instance of the cyberspace to be studies will be World of Warcraft (WoW), which is a Massively Multiplayer Online Role-Playing Game (MMORPG). WoW has been one of the most popular online cyberspace examples, whith its over ten million subscribers worldwide, and it provides its players with an absolute environment for social interaction. Thus this model of cyberspace would be the most suitable text for this study to look at the general relations between visual images and players in online cyberspace."